KEDUDUKAN ANAK ANGKAT SEBAGAI AHLI WARIS BERDASARKAN KOMPILASI HUKUM ISLAM (STUDI KASUS PUTUSAN NOMOR 2142/PDT.G/2017/PA.PLG) - Maharesi Trifo Putra; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2021)
Based on Article 171 letter h of the compilation of Islamic law, it is stated that an adopted child is a child who in terms of maintenance for their daily life, education costs and etc, their responsibilities shift from their original parents to their adoptive parents based on a court decision. In fact, Islam supports the existence of child protection services, one of them is by adopting children. The Compilation of Islamic Law emphasizes that adopted children or adoptive parents have no inherited relationship, but as an acknowledgment of the institution of adoption, the relationship between the adopted child and their adoptive parents is conveyed through the intermediary of a will or testament obligatory. The compilation of Islamic law which is now a reference by the religious courts that adopted children are entitled to a mandatory will on the condition that it cannot be more than 1/3 (one third) of the inheritance of the adoptive parents. The consideration of the judge who gave more than 1/3 of the assets based on the case Number 2142/Pdt.G/2017/PA.PLG is probably because since the baby the child was raised by their adoptive parents and they intended to split 2 land certificates and intends to give one of them to their adopted child during their life, but until they died it was not carried out and inheritance distribution does not reduce the share of the other heirs and there is even a remaining inheritance.